'That Was the Blunder': Moving House in Gaskell's North and South. (July 2022) - Wagner, Tamara S.
Abstract : Elizabeth Gaskell's North and South (1854–5) contains a structurally and thematically important narrative about moving house that prompts a much-needed recalibration of how we can read representations of domestic labour in Victorian fiction. Gaskell explores how homemaking is changing and perhaps needs to change in a modern, industrial world and how this can be expressed by dramatising the practicalities of house-moving. A close look at the representation of domestic labour – and how it is brought to a crisis through relocation – reveals a hitherto neglected aspect of the novel, while drawing attention to the representation of hands-on housework in Victorian literature. In plotting the practical tasks of house-moving in unprecedented detail, Gaskell renders the general speeding up of daily life concrete and relevant for her target readership. While interpolating practical advice, she also tests out how everyday, domestic challenges could, or should, be represented in fiction. An approach that takes the focus on housework in North and South seriously also resolves the supposed problem that domestic concerns pose in an industrial novel.